(untitled) (Konferensiyalar | Conferences, 2024)
The role of technology in the language learning journey has altered language acquisition process, making it more effective and meaningful. Technology has improved education by providing learners reliable resources, such as learning applications, online courses and virtual tutoring platforms. This article sheds light on the advantages of using technological tools in language learning and teaching.